Short-Term Impact of Drip Irrigation Frequency on Soil Hydro-Physical Properties of an Alfisol and Performance of Two Maize Varieties - Gabriel Oladele Awe; Busola Margret Ayuba; Japheth Umam; Toyin Peter Abegunrin (Turkish Journal of Agriculture: Food Science and Technology)
Irrigation scheduling is important for efficient use of applied water and for maximizing crop yields. Therefore, the aim of this study was to evaluate the short-term effect of drip irrigation frequency on soil hydro-physical properties of an Alfisol and performance of two maize varieties, at the Teaching and Research Farm, Faculty of Agricultural Sciences, Ekiti State University, Ado Ekiti, Southwest Nigeria. The experiment was laid out using a split-plot experiment in randomized complete block design (RCBD) and three replications. Irrigation frequency constituted the main plot namely: irrigation four times a week (I4), irrigation thrice a week (I3), and irrigation twice a week (I2) of re-filling soil to field capacity while the subplot was maize variety namely: V1: SAMMAZ-27 and V2: OBA-super-6. Plant growth parameters and soil physical properties of soil water content (SWC), bulk density (BD) and saturated hydraulic conductivity (Ksat) were monitored during the growing cycle. Water use efficiency (WUE) and yield components were determined at maturity. There were significant interactions between irrigation regime and maize variety on SWC and Ksat. The maximum bulk density (BDmax) and optimum soil water content SWCopt were 1.41 g/cm3 and 0.12 g/g, respectively. Plant height (PH) did not differ between the two maize varieties throughout the growth cycle. Drip irrigation frequency did not significantly affect plant height until growth stage V12 (12 fully opened leaves), with I4 irrigation treatment having the tallest plant. Both drip irrigation and maize variety had no significant influence on both LAI and CC, neither was there any significant interaction effect. Increasing irrigation water increased maize yield and yield components. The treatment combination of I4V1 had the highest performance indices in terms of yield components. WUE decreased with increasing frequency of irrigation water application while the WUE of SAMMAZ-27 > OBA-super-6. Therefore, irrigating four times a week and SAMAZ-27 maize variety could be a suitable irrigation-variety combination for providing sustainable irrigation agriculture for maize in this region.